13. ANALISIS KERJA SAMA BILATERAL INDONESIA DENGAN AUSTRALIA DALAM PENANGGULANGAN TERORISME SEBAGAI KEJAHATAN TRANSNASIONAL TERORGANISIR (2002-2015) - Shara Yosevina Simanjuntak; Tri Cahyo Utomo; andi Akhmad Basith Dir (Journal of International Relations Diponegoro, 2016)
9/11 Attack in the United States led to the international community alert to the threat ofterrorism. A year later, the first Bali bombing incident occurred in 2002 with the victim asmuch as 202 people from 22 countries, including 88 victims are Australians. It’s triggered thegovernments of Indonesia and Australia to cooperate on counter-terrorism. This researchintends to analyze 13 years of cooperation between the two governments under three differentpresidents of the Republic of Indonesia from the year 2002 to 2015. The framework used wasthe liberalism theory in international relations with international cooperation as the concept.This type of research is descriptive with qualitative data analysis techniques through datacollection from literature and documentation. This study found that the development ofcounter-terrorism cooperation between Indonesia and Australia are affected by the situation ofnational and international security, foreign policy, the background of each president, and thenational identity. The cooperation that has existed for the past 13 years show no significantdevelopment other than the establishment of JCLEC in 2004, so it’s necessary to form a new anew cooperation that is more preventive against the threat of terrorism in the future.